Tim-1-mediated extracellular matrix promotes the development of hepatocellular carcinoma - Hua Ruheng; Yu Pengfei; Zheng Wanting; Wu Nuwa; Yu Wangjianfei; Kong Qingyu; He Jun; Qin Lei (Acta Biochimica et Biophysica Sinica)
Tim-1 (T-cell immunoglobulin and mucin domain 1), also known as Kim-1 (kidney injury molecule 1) or hepatitis A virus cellular receptor 1 (HAVCR1), is a transmembrane protein expressed on various immune and epithelial cells. It plays a role in modulating inflammatory and immune responses. In this study, we find that Tim-1 is overexpressed in hepatocellular carcinoma (HCC) samples and that its expression is significantly correlated with postoperative survival. Bulk RNA sequencing reveals a general upregulation of extracellular matrix-related genes in HCC tissues with Tim-1 overexpression. The results of the cell and in vivo experiments reveal that Tim-1 in HCC not only affects biological processes such as the proliferation, migration, and invasion of HCC cells but also broadly promotes extracellular matrix processes by influencing cytokine secretion. Further studies demonstrate that Tim-1 mediates the activation of hepatic stellate cells and upregulates Th1 and Th2 cytokines, thereby promoting HCC progression. Thus, Tim-1 may represent a novel target for future interventions in HCC and liver fibrosis. <?Pub Caret 33?>